2013
DOI: 10.1080/03602559.2012.722740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silane Treatment on Mechanical Properties of Basalt Fiber/Polylactic Acid Ecofriendly Composites

Abstract: Ecofriendly thermoplastic composites combining basalt fiber and polylactic acid were prepared and analyzed, considering effects when the fiber is silane treated. Intended to improve mechanical properties of the composites, the silane treatment varied the types of silane solution (water-and methanol-based solvents) and immersion time (15 and 60 min). Optimum mechanical properties were exhibited by composite whose basalt fiber constituent was treated by silane dissolved in water-based solvent, for a short period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The general procedure applied for BF in the literature was used. 25 , 26 , 31 The silane treatment of BF was made as follows: 5 wt % three different silanes were injected in ethanol/water (1:1 by weight) mixture. The pH of AP, GP, and MA containing solutions are 11.1, 8.7, and 9.3, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general procedure applied for BF in the literature was used. 25 , 26 , 31 The silane treatment of BF was made as follows: 5 wt % three different silanes were injected in ethanol/water (1:1 by weight) mixture. The pH of AP, GP, and MA containing solutions are 11.1, 8.7, and 9.3, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies revealed that good improvements in the mechanical properties of inorganic fiber-reinforced thermoplastic polymer composites were obtained using silane coupling agents. [8][9][10][11][24][25][26][27][28][29][30][31][32][33] In the literature, various silane coupling agents were used in glass fiber-reinforced ABS composites. [8][9][10][11] Ozkoc et al investigated interfacial adhesion properties of different silane-modified short glass fiber-reinforced ABS/PA6 blends at the constant fiber ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the fibers surface treatment has become a necessary step in the preparation of the FRP [20,21]. Indeed, the state of adhesion between the fillers and the polymeric determines the performances of the resulting composite.…”
Section: Bfs Surface Treatmentmentioning
confidence: 99%
“…Compared to the available literature on basalt fiber as a material reinforcing thermoset resins and concretes, there are only several publications that have discussed the subject of thermoplastic composites reinforced with this fiber [21,22,23,24]. Few publications are also available on polylactide-basalt composites [25,26,27,28,29]. In spite of this, even the results of the quoted works show the large potential of basalt fiber as reinforcing filler, especially for a semi-crystalline matrix.…”
Section: Introductionmentioning
confidence: 99%